HIV incidence in western Kenya during scale-up of antiretroviral therapy and voluntary medical male circumcision: a population-based cohort analysis. Issue 5 (May 2018) - Borgdorff, Martien W; Kwaro, Daniel; Obor, David; Otieno, George; Kamire, Viviane; Odongo, Frederick; Owuor, Patrick; Muthusi, Jacques; Mills, Lisa A; Joseph, Rachael; Schmitz, Mary E; Young, Peter W; et al.
Summary: Background: In Kenya, coverage of antiretroviral therapy (ART) among people with HIV infection has increased from 7% in 2006, to 57% in 2016; and, in western Kenya, coverage of voluntary medical male circumcision (VMMC) increased from 45% in 2008, to 72% in 2014. We investigated trends in HIV prevalence and incidence in a high burden area in western Kenya in 2011–16. Methods: In 2011, 2012, and 2016, population-based surveys were done via a health and demographic surveillance system and home-based counselling and testing in Gem, Siaya County, Kenya, including 28 688, 17 021, and 16 772 individuals aged 15–64 years. Data on demographic variables, self-reported HIV status, and risk factors were collected. Rapid HIV testing was offered to survey participants. Participants were tracked between surveys by use of health and demographic surveillance system identification numbers. HIV prevalence was calculated as a proportion, and HIV incidence was expressed as number of new infections per 1000 person-years of follow-up. Findings: HIV prevalence was stable in participants aged 15–64 years: 15% (4300/28 532) in 2011, 12% (2051/16 875) in 2012, and 15% (2312/15 626) in 2016. Crude prevalences in participants aged 15–34 years were 11% (1893/17 197) in 2011, 10% (1015/10 118) in 2012, and 9% (848/9125) in 2016; adjusted for age and sex these prevalences were 11%, 9%, and 8%. 12 606 (41%) of the 30 520 non-HIV-infected individuals enrolled were seen again in at least one more survey round, and were included in the analysis of HIV incidence. HIV incidence was 11·1 (95% CI 9·1–13·1) per 1000 person-years from 2011 to 2012, and 5·7 (4·6–6·9) per 1000 person-years from 2012 to 2016. Interpretation: With increasing coverage of ART and VMMC, HIV incidence declined substantially in Siaya County between 2011 and 2016. VMMC, but not ART, was suggested to have a direct protective effect, presumably because ART tended to be given to individuals with advanced HIV infection. HIV incidence is still high and not close to the elimination target of one per 1000 person-years. The effect of further scale-up of ART and VMMC needs to be monitored. Funding: Data were collected under Cooperative Agreements with the US Centers for Disease Control and Prevention, with funding from the President's Emergency Fund for AIDS Relief.